Management Strategy in Improving Public Information Services at The Cilegon City Diskominfo - Noerisma, Mega Okta; Stiawati, Titi (Edusight International Journal of Multidisciplinary Studies, 2024)
The research focuses on strategic management in improving public information services at the Cilegon City Communication and Information Service. The problems studied in this study are the lack of human resource capacity in mastering information materials needed by the community, the provision of public information in electronic media, namely through websites, in terms of content is not complete and well updated, the lack of community participation in utilizing the freedom to obtain information, limited Human Resources (HR) in managing public information services. The purpose of this study is to determine Strategic Management in Improving Public Information Services at the Cilegon City Communication and Information Service. The theory used as a reference in this study is the strategic management theory put forward by Wheelen and Hunger (2012:15) consisting of 4 indicators, namely environmental observation, strategy formulation, strategy implementation, evaluation and control. This study uses a qualitative method with data analysis through interview results, observation, and documentation. The results of the study show that Strategic Management in Improving Public Information Services at the Cilegon City Communication and Information Office still has challenges that need to be overcome. Increasing understanding of resource capabilities, website development, and community participation requires further attention to achieve more optimal and effective public information management.